Application of Anaerobic Aerobic Biofilter Systems for Reducing Organic Matter in Cracker-Wastewater Treatment - Abdulgani, Hamdani; Hadiyanto, Hadiyanto; Sudarno, Sudarno; Fadhil, Muhammad (Universitas Diponegoro, 2025)
Wastewater treatment using traditional systems is considered expensive because it requires considerable energy and installation. The current study assessed the existence of a combination process that can reduce costs and is easy to operate. This study evaluates the performance of an anaerobic-aerobic biofilter system to treat industrial wastewater from cracker production. The combination of anaerobic and aerobic biofilters can significantly reduce Biochemical Oxygen Demand (BOD) and Chemical Oxygen Demand (COD), which are important parameters for wastewater quality. Sampling was carried out on the influent channel of the fish cracker industry. Sampling uses the SNI 6989.59:2008 regulation in the form of a wastewater test sampling method. The results showed that the biofilter achieved BOD removal of up to 84.90% and COD reduction of more than 89.02% when operated with an extended Hydraulic Retention Time (HRT) of up to 24 h. The results also showed that in wastewater treatment, HRT optimization should be considered for maximum pollutant removal, as shorter retention times proved less effective in reducing COD and BOD organic loads. These findings suggest that anaerobic-aerobic biofilter systems are viable and scalable solutions for industries seeking efficient and environmentally friendly wastewater treatment options.